Impact of meningococcal group B OMV vaccines, beyond their brief - Helen Petousis-Harris (Human Vaccines & Immunotherapeutics, 2018)
Meningococcal group B outer membrane vesicle vaccines have been used widely in Cuba, New Zealand, and Brazil. They are immunogenic and initially assessed largely by their ability to induce serum bactericidal activity. Measures of efficacy indicate good protection against homologous strains in older children and adults. Effectiveness appears broader than predicted by immunogenicity and efficacy studies. The recent discovery that meningococcal group B OMVs may protect against the related Neisseria species N.gonorrhoeae suggests more to these interesting antigen collections than meets the eye. Currently there are two OMV-containing group B vaccines available, the new recombinant protein-based Bexsero® developed by Novartis and VA-MENGOC-BC® developed by the Finlay institute in Cuba. Also, a third group B vaccine based on two recombinant factor H binding proteins (Trumenba®, Pfizer), has recently been licenced but it does not include OMV. This commentary explores the population impact that group B OMV vaccines have had on meningococcal and gonorrhoea diseases. Given the heterologous effect against diverse strains of the meningococcus observed in older children and adults, and recent evidence to suggest moderate protection against gonorrhoea, there may be a role for these vaccines in programmes targeting adolescents and groups high at risk for both meningococcal disease and gonorrhoea.